Income redistribution in the European Union - Silvia Avram; Horacio Levy; Holly Sutherland (IZA Journal of European Labor Studies, 2014)
We explore the redistributive effects of taxes and benefits in the 27 member states of the European Union (EU) using EUROMOD, the tax-benefit microsimulation model for the EU. As well as describing redistributive effects in aggregate, we assess and compare the effectiveness of eight individual types of policy in reducing income disparities. We derive results for the 27 members of the EU using policies in effect in 2010 and present them for each country separately as well as for the EU as a whole.
Keywords: D31; H24; I38; 330; Redistribution; European Union; Microsimulation; Tax-benefit systems